Trait Mindfulness Decouples the Association Between System Justification and Racial Outgroup Attitudes - Price-Blackshear, Mollie A. (Race and social problems, 2023)
System justification theory suggests that high-status group members endorsing status hierarchies will favor their ingroup and may show less positive outgroup attitudes. Understanding which variables influence these relationships is important. We explored whether trait mindfulness would decouple the relationship between racial-system justification, negative ethnic attitudes, and other-group orientation, among samples of White Americans. Studies 1 and 2 suggested that trait mindfulness moderated (i.e., decoupled) the negative influences of system justification on the outcome variables. In some circumstances, intergroup anxiety mediated the findings for those low and moderate in trait mindfulness, as compared to those with high trait mindfulness. Our findings support the predictions of system justification theory but reveal that trait mindfulness can decouple the relationship between system justification and outgroup attitudes. This suggests that trait mindfulness may best serve as a moderator that decouples pernicious relationships, as compared to having direct influences on prejudice. These findings are important, because understanding factors which reduce prejudice are relevant given its persistence in the United States.